2018
DOI: 10.1007/s00268-018-4788-2
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Adrenal Venous Sampling in Patients with Bilateral Adrenal Masses and ACTH‐Independent Cushing’s Syndrome

Abstract: AVS was useful in excluding a unilateral adenoma as the source of AICS in this study of patients with bilateral adrenal masses and AICS. However, adrenal mass size influenced surgical decision making more than AVS results. More data are needed before AVS can be advocated as essential for management of patients with bilateral adrenal masses and AICS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 19 publications
1
16
0
2
Order By: Relevance
“…Therefore, AVS, which is used for the diagnosis and subtype confirmation of hyperaldosteronism, might be a useful diagnostic tool. 5 , 8 , 10 , 11 However, unlike PA, 10 the concentration of cortisol in adrenal adenoma is increased. Therefore, adrenal-to-peripheral venous cortisol concentrations cannot be used to confirm a correct catheter position.…”
Section: Discussionmentioning
confidence: 98%
“…Therefore, AVS, which is used for the diagnosis and subtype confirmation of hyperaldosteronism, might be a useful diagnostic tool. 5 , 8 , 10 , 11 However, unlike PA, 10 the concentration of cortisol in adrenal adenoma is increased. Therefore, adrenal-to-peripheral venous cortisol concentrations cannot be used to confirm a correct catheter position.…”
Section: Discussionmentioning
confidence: 98%
“…The results of this groundbreaking study have recently been questioned by Acharya et al (17) who, using criteria of Funder et al (16), failed to confirm the lateralization of adrenal adenomas, probably due to patient selection criteria as mentioned in the study (17). Instead, the group focused on the morphology identified at the computer tomography scan, and surgically excised accordingly the larger suprarenal multinodular gland, thus avoiding a life-altering bilateral suprarenalectomy.…”
Section: Current Diagnostic Criteria and Surgical Treatment Optionsmentioning
confidence: 92%
“…However, the source of excess cortisol in AICS could be localized using AVS. Multiple case reports have suggested that AVS may be used to successfully localize excess cortisol in patients with AICS (16,(33)(34)(35)(36)(37). In the case of a 40-year-old woman from China with a large pelvic mass, AVS also aided localization of ectopic AICS (15).…”
Section: Adrenocorticotropic Hormone Independent Cushing Syndromementioning
confidence: 99%